Atom-economical synthesis of γ-valerolactone with self-supplied hydrogen from methanol. Issue 91 (25th September 2015) - Li, Zheng; Tang, Xing; Jiang, Yetao; Wang, Yanjun; Zuo, Miao; Chen, Wei; Zeng, Xianhai; Sun, Yong; Lin, Lu
Abstract : An atom-economical Cu–Cr catalyzed synthesis of gamma-valerolactone (GVL) from biomass derived methyl levulinate (ML) is reported. Methanol is occupied as H2 source with an initial amount of only 29 mol% of substrate and, can be in situ supplied along with the generation of GVL. Abstract : γ-Valerolactone (GVL), a versatile biomass derived platform molecule, was synthesized with a highest yield of 89.8% from methyl levulinate (ML) using self-supplied H2 coming from the decomposition of MeOH derived partially from ML. Cu–Cr acted as a bi-functional catalyst for both H2 production from MeOH and carbonyl hydrogenation. An extremely low amount of MeOH (29 mol% relative to ML) was initially necessary to start up the hydrocyclization of ML to GVL and MeOH, which is in turn employed as an in situ H2 source for ML hydrogenation, providing an atom-economical pathway for GVL production.